Austenitic stainless steel cold-rolled and annealed steel sheet with improved deep drawability
By controlling the composition of austenitic stainless steel, satisfying the formula for the proportion of specific elements, and suppressing the transformation of martensite phase, the problems of increasing strength and local stress concentration in deep-tighting processing are solved, and the stable deep-tighting processing effect is achieved.
Patent Information
- Application Number
- JP2023512177
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-31
- Filing Date
- 2021-07-23
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2041-07-23
Smart Images

Figure 0007624506000004 
Figure 0007624506000005 
Figure 0007624506000001
Abstract
Description
[Technical field]
[0001] The present invention is an austenitic stainless steel with improved deep drawing properties. Cold rolled and annealed steel sheet More specifically, the present invention relates to an austenitic stainless steel having improved deep drawability that does not generate cracks when deep drawing is applied to convert sheet material into three-dimensional parts. Cold rolled and annealed steel sheet Regarding. [Background technology]
[0002] Recently, as competition in product prices has intensified, there has been a demand for cost reduction in materials used for parts. Deep drawing is an effective method for reducing manufacturing costs because it can eliminate additional processes such as welding, stress relief heat treatment, etc. Meanwhile, when cylindrical molding is involved, such as in cups and batteries, materials with excellent deep drawability are required. Austenitic stainless steel has excellent elongation properties, making it easy to create complex shapes, and has excellent work hardening ability, making it a type of steel that is used in a variety of fields involving deep drawing. In general, austenitic stainless steel undergoes deformation during cold working while undergoing work hardening, and it is known that austenitic stainless steel with excellent work hardening ability is easy to form.
[0003] However, when applying deep drawing to austenitic stainless steel, the strength of the material increases continuously due to work hardening, which causes local stress concentration in the material, eventually resulting in breakage. Meanwhile, in order to solve the problem of strength increase due to work hardening, it is possible to consider introducing intermediate heat treatment, but this is limited in terms of process time / process cost. Therefore, there is a need for the development of an austenitic stainless steel that can be used as a material for deep drawing by eliminating the intermediate heat treatment step and minimizing the increase in strength due to work hardening when deep drawing is applied. Summary of the Invention [Problem to be solved by the invention]
[0004] The object of the present invention is to provide an austenitic stainless steel that can ensure formability when deep drawing is applied by minimizing the increase in strength due to work hardening. Cold rolled and annealed steel sheet The purpose of this project is to provide [Means for solving the problem]
[0005] Austenitic stainless steel with improved deep drawability according to the present invention Cold rolled and annealed steel sheet contains, by weight percent, C: 0.01-0.05%, N: 0.01-0.25%, Si: 1.5% or less (0 is excluded), Mn: 0.3-3.5%, Cr: 17.0-22.0%, Ni: 9.0-14.0%, Mo: 2.0% or less (0 is excluded), Cu: 0.2-2.5%, and the remainder is Fe and unavoidable impurities, and satisfies the following formula (1). Formula (1): Cr+Si+2*Mo+3*(Ni+Cu)+50*(C+N)≧63 Here, Cr, Si, Mo, Ni, Cu, C, and N mean the weight percentage of each element.
[0006] Furthermore, according to the present invention, the following formula (2) can be satisfied. Formula (2): 0<2.4*Cr+1.7*Mo+3.9*Si-2.1*Ni-Mn-0.4*Cu-58*C-64*N-13<5.5 Here, Cr, Mo, Si, Ni, Mn, Cu, C, and N mean the weight percentage of each element.
[0007] In addition, according to the present invention, one or more of Al: 0.04% or less (0 is excluded), Ti: 0.003% or less (0 is excluded), B: 0.0025% or less (0 is excluded), P: 0.035% or less, and S: 0.0035% or less may be further included. According to the present invention, the true strain rate value when the work hardening exponent is maximum in the following formula (3) may be 0.2 or less. Equation (3): σ = Kε n Here, σ is stress, K is strength coefficient, ε is strain rate, and n is work hardening exponent.
[0008] According to the present invention, the difference between the true strain rate value when the work hardening exponent is maximum and the true strain rate value when the work hardening exponent is 0 is 0.11 or more; The elongation rate is 35% or more, The tensile strength is 360 MPa or more, When multi-stage molding is performed under conditions of a drawing ratio of 1.7 to 4.3, cracks may not occur up to five stages of molding. Effect of the Invention
[0009] According to the present invention, an austenitic stainless steel that can be used as a material for deep drawing can be obtained by omitting an intermediate heat treatment process when applying deep drawing and by minimizing the increase in strength due to work hardening. Cold rolled and annealed steel sheet can be provided. [Brief description of the drawings]
[0010] [Figure 1] 1 is a graph for explaining the relationship between stress and strain rate in a tensile experiment of a material. [Diagram 2] 1 is a graph showing the relationship between stress and strain rate during tensile testing of an austenitic stainless steel according to a disclosed embodiment, together with the work hardening exponent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Austenitic stainless steel with improved deep drawability according to the present invention Cold rolled and annealed steel sheet contains, by weight percent, C: 0.01-0.05%, N: 0.01-0.25%, Si: 1.5% or less (0 is excluded), Mn: 0.3-3.5%, Cr: 17.0-22.0%, Ni: 9.0-14.0%, Mo: 2.0% or less (0 is excluded), Cu: 0.2-2.5%, and the remainder is Fe and unavoidable impurities, and satisfies the following formula (1). Formula (1): Cr+Si+2*Mo+3*(Ni+Cu)+50*(C+N)≧63 Here, Cr, Si, Mo, Ni, Cu, C, and N mean the weight percentage of each element.
[0012] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings. The following embodiments are presented to fully convey the concept of the present invention to those skilled in the art to which the present invention pertains. The present invention is not limited to the embodiments presented herein and may be embodied in other forms. In the drawings, parts that are not relevant to the description may be omitted in order to clarify the present invention, and the size of components may be exaggerated to facilitate understanding. Furthermore, when any part is said to "comprise" a certain component, this does not mean to exclude other components, but rather that it may further include other components, unless specifically stated to the contrary. The singular expression includes the plural expression unless the context clearly dictates otherwise.
[0013] The present invention will now be described in detail with reference to the accompanying drawings. Austenitic stainless steel has a high elongation rate and excellent formability, making it a type of steel used for products of various shapes. When austenitic stainless steel is subjected to stress, it undergoes deformation due to transformation induced plasticity, that is, transformation from the austenite phase, which is unstable at room temperature, to the martensite phase. At this time, the martensite phase that is generated has high strength, so the strength of the material also increases. In other words, in austenitic stainless steel, deformation and strength increase occur simultaneously due to work-hardening. Work-hardening capacity is expressed using the work-hardening exponent, which changes depending on the strain rate. It is known that austenitic stainless steels have excellent work hardening ability and are therefore easy to form. However, when deep drawing is performed while reducing the blank diameter on austenitic stainless steel, the strength increases continuously due to work hardening, which causes local stress concentration in the material, eventually resulting in breakage.In addition, cracks may suddenly occur after forming due to aging cracking. Therefore, in deep drawing, which involves a large amount of deformation, it is important that deformation occurs uniformly throughout the material and that changes in strength during deformation are minimized. In other words, in order to improve the deep drawability of austenitic stainless steel, it is necessary to suppress work hardening.
[0014] On the other hand, the work hardening of austenitic stainless steels is related to the stability of the austenite phase. By increasing the stability of the austenite phase through composition control, the work hardening of austenitic stainless steels can be suppressed. However, since the workability of austenitic stainless steel, as represented by the elongation rate, is derived from the work hardening caused by plastic organic transformation, there is a problem that a reduction in the work hardening ability reduces the workability of austenitic stainless steel.
[0015] The present inventors conducted various investigations to ensure the elongation rate of austenitic stainless steel and to suppress an increase in strength due to work hardening when deep drawing is applied, and as a result, they obtained the following findings. In the present invention, as a result of examining factors for preventing breakage during deep drawing in austenitic stainless steel, it has been discovered that the deep drawing of austenitic stainless steel can be improved by suppressing the transformation of martensite phase due to stress to prevent excessive work hardening, and by ensuring a certain amount of deformation without an excessive increase in strength. This can be achieved by deriving an alloy composition system that can ensure continuous deformation without an excessive increase in strength. An austenitic stainless steel with improved deep drawability according to one aspect of the present invention contains, by weight, C: 0.01-0.05%, N: 0.01-0.25%, Si: 1.5% or less (0 is excluded), Mn: 0.3-3.5%, Cr: 17.0-22.0%, Ni: 9.0-14.0%, Mo: 2.0% or less (0 is excluded), Cu: 0.2-2.5%, and the remainder consisting of Fe and unavoidable impurities.
[0016] The reasons for limiting the contents of the alloying elements in the present invention will be described below. In the following, the unit is weight percent unless otherwise specified. The C content is 0.01 to 0.05%. Carbon (C) is an effective element for stabilizing the austenite phase, and can be added in an amount of 0.01% or more to suppress the formation of martensite phase during deformation and ensure strength. However, if the content is excessive, it can combine with Cr to induce grain boundary precipitation of Cr carbide, which reduces corrosion resistance, so the upper limit can be limited to 0.05%. The N content is 0.01 to 0.25%. Nitrogen (N), like carbon, is an effective element for stabilizing the austenite phase, and can be added at 0.01% or more to ensure deep drawability. However, if the content is excessive, it can form nitrides that degrade the surface quality, so the upper limit can be limited to 0.25%.
[0017] The Si content is 1.5% or less (excluding 0). Silicon (Si) is an element that acts as a deoxidizer during the steelmaking process and ensures the strength and corrosion resistance of austenitic stainless steel. However, if the content of silicon, which is an element that stabilizes the ferrite phase, is excessive, it promotes the transformation of the martensite phase and precipitates intermetallic compounds such as the σ phase, which reduces mechanical properties and corrosion resistance. Therefore, in the present invention, the upper limit can be limited to 1.5%. The Mn content is 0.3 to 3.5%. Manganese (Mn), like carbon (C) and nitrogen (N), is an element that stabilizes austenite and has the effect of suppressing the increase in strength that occurs during forming, so it can be added in an amount of 0.3% or more. However, if the content is excessive, it can form excessive amounts of S-based inclusions (MnS), which can reduce the corrosion resistance and surface gloss of austenitic stainless steel, so the upper limit can be limited to 3.5%. The Cr content is 17.0-22.0%. Chromium (Cr) is the most abundant and basic element that stabilizes ferrite and improves the corrosion resistance of stainless steel. In the present invention, 17.0% or more of chromium can be added to form a passivation film that suppresses oxidation and ensures corrosion resistance. However, if the content of chromium, which is a stabilizing element of the ferrite phase, is excessive, the stability of the austenite phase decreases and the transformation of martensite is promoted, which leads to an increase in the nickel content, thereby increasing the manufacturing cost, and there are problems in that intermetallic compounds such as σ phase are precipitated, resulting in deterioration of mechanical properties and corrosion resistance. Therefore, in the present invention, the upper limit of chromium can be limited to 22.0%.
[0018] The Ni content is 9.0 to 14.0%. Nickel (Ni) is the most powerful austenite phase stabilizing element, and as its content increases, the austenite phase becomes more stable, softening the material and suppressing work hardening caused by the generation of deformed organic martensite. In order to do so, it is essential to add 9% or more. However, Ni is an expensive element, and adding a large amount of it increases the cost of raw materials. Therefore, taking into consideration both the cost and efficiency of the steel material, the upper limit can be set to 14.0%. The Mo content is 2.0% or less (0 is excluded). Molybdenum (Mo) is an element that is effective in improving the corrosion resistance of steel. However, if the content of molybdenum, which is an element that stabilizes the ferrite phase, is excessive, the stability of the austenite phase decreases, making it difficult to ensure deep drawability, and the mechanical properties and corrosion resistance decrease due to the precipitation of intermetallic compounds such as σ phase. Therefore, in the present invention, the upper limit of the molybdenum content can be limited to 2.0%.
[0019] The Cu content is 0.2-2.5%. Copper (Cu) is an austenite phase stabilizing element added in place of expensive nickel (Ni), and can be added at 0.2% or more to ensure price competitiveness and deep drawability. However, if the content is excessive, a low melting point ε-Cu precipitate phase is formed, which can degrade surface quality, so the upper limit can be limited to 2.5%. In addition, according to one embodiment of the present invention, one or more of Al: 0.04% or less (0 is excluded), Ti: 0.003% or less (0 is excluded), B: 0.0025% or less (0 is excluded), P: 0.035% or less, and S: 0.0035% or less may be further included. The Al content is 0.04% or less (0 is excluded). Aluminum (Al) is a powerful deoxidizing agent that reduces the oxygen content in molten steel. However, if its content is excessive, it can cause sleeve defects in cold rolled strips due to an increase in nonmetallic inclusions, so its upper limit can be set to 0.04%. The Ti content is 0.003% or less (0 is excluded). Titanium (Ti) is an element that is effective in ensuring the corrosion resistance of steel by preferentially combining with interstitial elements such as carbon (C) and nitrogen (N) to form precipitates (carbonitrides), thereby reducing the amount of dissolved C and N in steel and suppressing the formation of Cr-depleted regions. However, if its content is excessive, it forms Ti-based inclusions, which make manufacturing difficult and can cause surface defects such as scabs, so the upper limit can be limited to 0.003%.
[0020] The B content is 0.0025% or less (excluding 0). Boron (B) is an effective element for suppressing crack generation during casting and ensuring good surface quality. However, if its content is excessive, it can form nitrides (BN) on the product surface during the annealing / pickling process, degrading the surface quality, so its upper limit can be limited to 0.0025%. The P content is 0.035% or less. Phosphorus (P) is an impurity that is inevitably contained in steel and is a major cause of grain boundary corrosion or of impairing hot workability, so it is preferable to control the P content as low as possible. In the present invention, the upper limit of the P content is controlled to 0.035%. The S content is 0.0035% or less. Sulfur (S) is an impurity that is inevitably contained in steel and is an element that is a major cause of impairing hot workability by segregating at grain boundaries, so it is preferable to control the S content as low as possible. In the present invention, the upper limit of the S content is controlled to 0.0035% or less. The remaining component of the present invention is iron (Fe). However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment, and it is not possible to exclude them. Since any engineer of a normal manufacturing process would know about these impurities, the contents of all of them will not be mentioned in this specification.
[0021] As described above, the work hardening of austenitic stainless steel occurs when the austenite phase, which is unstable at room temperature, transforms into the martensite phase due to stress caused by plastic deformation. As deformation continues, continuous phase transformation occurs, and this phase transformation increases the strength of austenitic stainless steel materials until they break. However, in order to ensure deep drawability, it is necessary to suppress the transformation of the martensite phase. In the present invention, the following formula (1) was derived in consideration of the phase transformation that occurs due to deformation of austenitic stainless steel. Specifically, the present invention aims to increase the stability of the austenite phase by increasing the content of austenite stabilizing elements such as Mn, N, Cu, and Ni, thereby suppressing the phase transformation to the martensite phase and the work hardening of the austenitic stainless steel. Formula (1): Cr+Si+2*Mo+3*(Ni+Cu)+50*(C+N) Here, Cr, Si, Mo, Ni, Cu, C, and N mean the weight percentage of each element.
[0022] The austenitic stainless steel with improved deep drawability according to the present invention satisfies the range of the value expressed by formula (1) of 63 or more. The inventors have confirmed that the lower the value of formula (1), the greater the change in strength that occurs during deformation due to external stress. Specifically, when the value of formula (1) is less than 63, austenitic stainless steels having the above-mentioned alloy composition exhibit rapid deformation-induced martensitic transformation behavior or plasticity variation occurs due to twin formation due to external deformation. This causes a problem of reduced elongation rate and deep drawability during multi-stage forming of austenitic stainless steels, so it is intended to limit the lower limit of formula (1) to 63. FIG. 1 is a graph illustrating the relationship between stress and strain rate in a tensile experiment of a material. The increase in strength due to work hardening can be explained by the stress-strain rate curve in Figure 1. In Figure 1, the work-hardening exponent (n), which indicates the degree of work hardening ability, can be expressed as follows: σ = Kε n Here, σ is stress, K is strength coefficient, and ε is strain rate.
[0023] On the other hand, if the common logarithm is applied to both sides of the above relational expression to express it as a log relational expression, it can be expressed as follows. logσ=logK+n*logε In other words, in the logarithmic relationship of stress-strain rate, the work hardening exponent n corresponds to the slope of the graph, and the greater the slope, the greater the increase in strength of the material during plastic deformation. In the present invention, in order to improve the deep drawability of austenitic stainless steel, it is necessary to ensure continuous deformation without excessive increase in strength, and the following formula (2) has been derived. Formula (2):2.4*Cr+1.7*Mo+3.9*Si-2.1*Ni-Mn-0.4*Cu-58*C-64*N-13 Here, Cr, Mo, Si, Ni, Mn, Cu, C, and N mean the weight percentage of each element. In the austenitic stainless steel with improved deep drawability according to one embodiment of the present invention, the value expressed by the above formula (2) satisfies the range of 0 to 5.5.
[0024] The inventors have confirmed that the higher the value of formula (2), the easier the martensitic transformation due to external stress occurs, which then causes an excessive increase in strength and reduces formability. Specifically, when the value of formula (2) is 5.5 or more, there is a problem that a continuous increase in strength occurs until just before breakage during tensile deformation, causing a sudden breakage. As a result, there is a problem that the elongation rate cannot be secured, so the upper limit of formula (2) is limited to 5.5. On the other hand, it was confirmed that if the value of formula (2) is too low, it becomes difficult for cross slip of the austenite phase to occur due to external stress. Specifically, when the value of formula (2) is less than 0, the austenitic stainless steel only exhibits planar slip behavior in response to deformation, and the accumulation of potential due to external stress progresses, resulting in plastic scatter and high work hardening. This causes a problem of reduced elongation and yield ratio of the austenitic stainless steel, so it is attempted to limit the lower limit of the value of formula (2) to 0. FIG. 2 is a graph showing the relationship between stress and strain rate during tensile testing of an austenitic stainless steel according to a disclosed embodiment, together with the work hardening exponent.
[0025] On the other hand, the austenitic stainless steel with improved deep drawability according to the present invention may have a true strain rate value of 0.2 or less when the work hardening exponent is at a maximum. In FIG. 2, A indicates the point where the work hardening exponent is maximum, and B indicates the point where the work hardening exponent is 0. Referring to Figure 2, it can be seen that the work hardening exponent decreases even as deformation progresses after point A. In other words, it can be seen that the strength increases gradually from point A to point B. In the present invention, in order to improve the deep drawability of austenitic stainless steel, it is necessary to ensure a certain amount of deformation without an excessive increase in strength, and it has been derived that point A, where the increase in strength is greatest, is located at a relatively low amount of deformation, and a certain amount of deformation must be ensured from point A to reach point B. The austenitic stainless steel with improved deep drawability according to the disclosed embodiment has a true strain rate of 0.2 or less when the work hardening exponent is at a maximum.
[0026] In FIG. 2, if the deformation value, which is the X coordinate of point A showing the maximum work hardening index, is derived to be 0.2 or less, the occurrence of excessive work hardening during deep drawing can be suppressed. In the austenitic stainless steel with improved deep drawability according to the disclosed embodiments, the difference between the true strain rate value when the work hardening index is maximum and the true strain rate value when the work hardening index is 0 is 0.11 or more. In other words, if it is possible to exhibit the maximum work hardening exponent at a small deformation amount and ensure sustained deformation without excessive increase in strength, it will be possible to ensure the elongation rate of austenitic stainless steel and prevent the occurrence of cracks when it is subjected to multi-stage processing of two or more stages. The austenitic stainless steel with improved deep drawability according to the disclosed embodiment, which satisfies the above-mentioned composition ranges of alloying elements and relational expressions, can ensure an elongation rate of 35% or more and a tensile strength of 360 MPa or more. Furthermore, in the austenitic stainless steel with improved deep drawability according to the satisfactory disclosed embodiments, no cracks occur up to five stages in two or more stages of forming under conditions of a drawing ratio of 1.7 to 4.3.
[0027] The present invention will now be described in more detail with reference to preferred embodiments. Working Example Using the composition ranges in Table 1 below, a 200 mm thick slab was produced through a continuous casting process, heated at 1,250°C for 2 hours, and then hot rolled to a thickness of 6 mm. After hot rolling, hot rolling annealing was performed at 1,150°C and coiled. The hot rolled coil was then cold rolled twice to a thickness of 1 mm and cold rolling annealed. Cold rolling was performed at a rolling reduction of 30-70% per pass, and cold rolling annealing was performed in a heating furnace at a temperature of 1100-1200°C for 5 minutes or less. In Table 1 below, the values in formulas (1) and (2) are values derived by substituting the weight percentage of each alloying element into formulas (1) and (2) below. Formula (1): Cr+Si+2*Mo+3*(Ni+Cu)+50*(C+N) Formula (2):2.4*Cr+1.7*Mo+3.9*Si-2.1*Ni-Mn-0.4*Cu-58*C-64*N-13
[0028] [Table 1]
[0029] The number of multi-stage forming times and work hardening index were measured for each steel sheet. Specifically, deep drawing was performed in five stages using a blank with a diameter of 85 mm, a first-stage punch with a diameter of 50 mm, a second-stage punch with a diameter of 38 mm, a third-stage punch with a diameter of 30 mm, a fourth-stage punch with a diameter of 24 mm, and a fifth-stage punch with a diameter of 20 mm. The drawing ratios for each stage were 1.7 for the first stage, 2.2 for the second stage, 2.8 for the third stage, 3.5 for the fourth stage, and 4.3 for the fifth stage. At each stage, the maximum number of molding cycles was set based on the case where no cracks occurred within 48 hours after molding of the processed product, and is shown in Table 2 below. Next, a tensile experiment was conducted according to the standard for JIS No. 13B tensile test piece, and the true stress-true strain rate was calculated from the stress-strain rate value obtained as the experimental result. The maximum work hardening index (a), the true strain rate value when the work hardening index is maximum (b), the true strain rate value when the work hardening index is 0 (c), and the difference between the true strain rate value when the work hardening index is maximum (b) and the true strain rate value when the work hardening index is 0 (c) are derived and listed in Table 2 below. In addition, the tensile strength (MPa) and elongation (%) measured from the results of the tensile test are shown in Table 2 below.
[0030] [Table 2] TIFF0007624506000003.tif90152
[0031] Referring to Table 2, it was confirmed that in the case of Examples 1 to 23, which satisfy the alloy composition, the value of formula (1), and the range of the value of formula (2) proposed by the present invention, it is possible to ensure not only a tensile strength of 350 MPa or more, but also an excellent elongation rate of 35% or more. In addition, when forming in two or more stages under the condition of a drawing ratio of 1.7 to 4.3, no cracks occur up to five stages, so it is applicable to fields where deep drawing of complex shapes is required. In Comparative Examples 1 to 6 and 17 to 21, the value of formula (1) did not reach 63, indicating a continuous increase in strength during work hardening, and the value of formula (2) exceeded 5.5, indicating that martensitic transformation due to deformation actively occurred, resulting in frequent cracking during multi-stage forming. In Comparative Examples 7 to 16, the value of formula (1) did not reach 63, and the value of formula (2) did not reach 0, so a sudden increase in strength occurred due to twin crystal formation during processing. The increase in strength due to twin crystal formation continued depending on the amount of deformation, which caused stress variations during deep drawing, making it impossible to ensure a sufficient forming depth. In this manner, according to the disclosed embodiments, by controlling the alloy components and the relational expressions, it is possible to produce an austenitic stainless steel that does not generate cracks up to five stages of forming when forming in two or more stages under conditions of a drawing ratio of 1.7 to 4.3, and that has an elongation rate of 35% or more and a tensile strength of 360 MPa or more.
[0032] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and it should be understood that various changes and modifications can be made by those skilled in the art without departing from the concept and scope of the following claims. [Industrial Applicability]
[0033] The present invention can be used in a variety of industrial fields, including fields involving deep drawing.
Claims
1. In weight percent, it contains C: 0.01-0.05%, N: 0.01-0.25%, Si: 1.5% or less (0 is excluded), Mn: 0.3-3.5%, Cr: 17.0-22.0%, Ni: 9.0-14.0%, Mo: 2.0% or less (0 is excluded), Cu: 0.2-2.5%, Al: 0.04% or less (0 is excluded), Ti: 0.003% or less (0 is excluded), B: 0.0025% or less (0 is excluded), P: 0.035% or less, and S: 0.0035% or less, with the remainder being Fe and unavoidable impurities, The following formulas (1) and (2) are satisfied: A cold-rolled annealed austenitic stainless steel sheet having improved deep drawability, characterized in that the true strain rate when the work hardening exponent is maximum in the following formula (3) is 0.2 or less. Formula (1): Cr+Si+2*Mo+3*(Ni+Cu)+50*(C+N)≧63 Formula (2): 0<2.4*Cr+1.7*Mo+3.9*Si-2.1*Ni-Mn-0.4*Cu-58*C-64*N-13<5.5 Formula (3): σ=Ke n (In the above formulas (1) and (2), Cr, Si, Mo, Ni, Mn, Cu, C, and N represent the weight percentage of each element.) (In the above formula (3), σ is stress, K is strength coefficient, ε is true strain rate, and n is work hardening exponent.)
2. The austenitic stainless cold-rolled annealed steel sheet with improved deep drawability according to claim 1, characterized in that the difference between the true strain rate value when the work hardening index is maximum and the true strain rate value when the work hardening index is 0 is 0.11 or more.
3. 2. The austenitic stainless cold-rolled annealed steel sheet with improved deep drawability according to claim 1, characterized in that the elongation is 35% or more.
4. 2. The austenitic stainless cold-rolled annealed steel sheet with improved deep drawability according to claim 1, characterized in that the tensile strength is 360 MPa or more.
5. The austenitic stainless cold-rolled annealed steel sheet with improved deep drawability according to claim 1, characterized in that no cracks occur up to five stages of forming when multistage forming is performed under a drawing ratio condition of 1.7 to 4.3.
Citation Information
Patent Citations
Free cutting austenite stainless steel with superior press formability
JP1983003954A
Nonmagnetic stainless steel excellent in surface property and production thereof
JP1995113144A
High strength stainless steel material for working having excellent hydrogen embrittlement resistance, stainless steel wire thereof and stainless steel formed part
JP2011208269A
Austenitic stainless steel with excellent workability and resistance of season cracking
KR1020190065720A
High hardness austenitic stainless steel with excellent corrosion resistance
KR1020190066734A